RUANG LINGKUP PERLINDUNGAN DATA PRIBADI: KAJIAN HUKUM POSISTIF INDONESIA - Muhammad Fikri; Shelvi Rusdiana (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2023)
The escalation of technology use in various lines of human life poses a new challenge to efforts to protect privacy and personal data in Indonesia. In addition, changes in procedures for collecting, managing, and disseminating data are developing very quickly, from the manual stage to the digitization movement. However, the increase in technological literacy rates has backfired for digital users due to the spike in cases of personal data leakage reaching 143% in 2022. In order to answer this phenomenon, the presence of law becomes the master key in providing personal data protection for users, either preventively or repressively. The focus of his research refers to the substance of Law Number 11 of 2008 or Law Number 19 of 2016 concerning Information and Electronic Transactions, hereinafter referred to as the ITE Law, and Civil Law as a form of national legal pluralism. Not only that, ownership of personal data can also be equated as material rights because of the droit de suite principle. With this material right, if an unlawful act (PMH) occurs as Article 1365 of the Civil Code, compensation can be demanded for the mistake. Furthermore, the purpose of this study is to analyze and understand how the perspective of Civil Law and the ITE Law regarding the protection of personal data in Indonesia. Then, the research method used is the normative juridical research method with various secondary data through the statute approach, conceptual approach, and analytical approach.